PENGEMBALIAN (REFUND) TIKET PESAWAT DALAM BENTUK VOUCHER BERDASARKAN PERSPEKTIF HUKUM PERJANJIAN PADA MASA PANDEMI COVID-19 - Tohpati Bimo Brahmantyo (2021)
Airline ticket refunds to provide legal certainty to passengers who experience flight cancellations due to the Covid-19 pandemic that is all over the world, especially in Indonesia. Mechanisms and provisions regarding flight ticket refunds in the airplane ticket agreement are based on the Peraturan Menteri Perhubungan Nomor PM 185 Tahun 2015 Tentang Standar Pelayanan Penumpang Kelas Ekonomi Angkutan Udara Niaga Berjadwal Dalam Negeri, but specifically for flight cancellations from April 24, 2020 to 31 In May 2020 a special Minister of Transportation was made which regulates the provisions for refunding airline tickets, Peraturan Menteri Perhubungan Nomor PM 25 Tahun 2020 Tentang Pengendalian Transportasi Selama Masa Mudik Idul Fitri 1441 Hijriah Dalam Rangka Pencegahan Penyebaran Corona Virus Desease (Covid-19). The formulation of the problem in this study, namely how is the refund clause of airplane tickets in the standard ticket sale and purchase agreement ? and what are the conditions for refunding airline tickets during the Covid-19 pandemic based on the perspective of the ticket sale and purchase agreement ? This study uses a normative juridical research method. The results of this study are knowing that the standard clause policy regarding refunds on each airline has differences, the Permenhub which regulates refunds during the Covid-19 pandemic has several ways to process refunds, but airlines determine unilaterally that ticket refunds are given in the form of vouchers not using the options that have been determined and the flight ticket refund mechanism carried out by airlines during the Covid-19 pandemic is not in accordance with the agreement and Permenhub No PM 25 of 2020 because the Permenhub explains ticket refunds by rescheduling, changing routes, compensation in the form of points, and vouchers, but the airline unilaterally stipulates that the refund will be carried out in the form of a voucher without regard to the refund methods contained in the agreement and the Permenhub.